Redeem Policy Implementation In Uganda By Takling The Political Question - Uganda Development Management Policy Forum (My University, 2014)
For many poor countries, especially in Africa, decision-making and policy formulation appear to be the easier job. Moving from policy making to policy execution and providing public goods and services is the tougher task. Many African countries, including Uganda, have made modest but significant advances in entrenching participatory politics, election management and institutionalizing the power to make decisions. However, there has been little progress in attaining socioeconomic transformation and improving the material conditions of the majority poor. Indeed some indicators of Uganda’ economy display improvement, though, the improvements do not tally with the actual, lived conditions of the wider Ugandan society. Many observers have lamented the poor record of policy implementation in a robust and thorough manner as the key reason for the continued dire socioeconomic conditions of Ugandans. Why has the modest progress in institutionalizing decision-making power and producing excellent policies not matched with the capacity to execute policies? What can be done to redeem policy implementation? This policy brief attempts to provide alternatives to this question.